Díaz Solimine, Omar L. (Dir.); Díaz Solimine, Ignacio L. (Coord.), El margen nacional de apreciación, Ciudad Autónoma de Buenos Aires, Astrea, 2020, 304 pp - Rosatti, Emilio (2020)
Fil: Rosatti, Emilio. Universidad Nacional del Litoral; Argentina